THU0438 Role of Calcium Crystals in Inflammation. Synovial Fluid Analysis by Scanning Electron Microscopy in Patients with Knee Osteoarthritis. Clinical and Laboratory Investigations in Different Phases of the Disease. (9th June 2015) - Frallonardo, P.; Oliviero, F.; Peruzzo, L.; Scanu, A.; Galozzi, P.; Lorenzin, M.; Ortolan, A.; Ramonda, R.; Punzi, L.
Abstract : Background: The role and the significance of calcium crystals (CC) in synovial inflammation and in Osteoarthritis (OA) progression is somewhat debated. Calcium pyrophosphate (CPP) and basic calcium phosphate (BCP) are the most common CC in OA. Objectives: The aim of this study was to evaluate the presence of CC in synovial fluid (SF) using ultrasensitive analysis by scanning electron microscopy (SEM) in the various stages of symptomatic and radiographic knee OA (KOA). Methods: One hundred twenty consecutive outpatients with KOA underwent knee arthrocentesis. Of these, 49 (40.8%) were in an early stage (<1 year). The SF samples were analyzed by compensated polarized light microscopy and SEM. Patients' medical history, clinical features, Kellgren Lawrence radiological score (KLRS), ultrasound power Doppler (USPD) signal were assessed. The Western Ontario and McMaster Universities OA Index (WOMAC) self-assessment questionnaire, the Lequesne algofunctional index (Lequesne) survey, and the visual analogic scale (VAS) forms were assessed in all patients. All the patients gave written informed consent. Results: CC were detected by SEM in 62/120 (51.6%) samples. The patients positive to CC (CC+) were older (p=0.036), had a greater difficulty in moving (p=0.0041), a higher SF PMN percentage (0.0041) and a higher USPD (p≤0.0001) with respect to the group of patients negative to CC (CC-). CPP crystals were positive in 37/120 patients (30%) by SEM. Age (p=0.0002), disease duration (p=0.041), pain (p=0.039), KLRS (p=0.0334) and USPD (p=0.0001) were significant different in the 2 groups of patients subdivided by the presence of CPP. BCP were detected in 33/120 patients (27.5%) by SEM. Subdividing patients by the presence of BCP, we found a significant differences as regard WOMAC (p=0.0001), pain (p=0.0001), stiffness (p<0.0001), functional impairment (p<0.0001), Lequesne index (p<0.0001), VAS (<0.0004) and USPD (p<0.0001). A correlation between KLRS and disease duration (DD) was found in the BCP+ group. The patients were then subdivided into three groups according to DD: I <1yr (N.49) early KOA; II 1-5 yrs (N.27); III >5 yrs (N.44) late KOA. Univariate analysis highlighted a significant difference in age and USPD. In the I group, patients BCP+ significant differences were found in pain (p=0.0002), stiffness (p=0.045), functional impairment (p=0.0014), WOMAC (p=0.0002) and USPD (p=0.0009), all higher with respect to patients negative to BCP. (Figure 1a, b, c ) Conclusions: The presence of CC was found to be correlated with a more severe clinical status, worse imaging findings, and positive USPD. The presence of BCP crystals in the early KOA group, which was associated to inflammatory aspects, suggests a possible role of BCP crystals in the pathogenesis of the disease. References: Scanzello CR, Goldring SR. The role of synovitis in osteoarthritis pathogenesis. Bone. 2012;51:249-57 Berenbaum F. Osteoarthritis as an inflammatory disease (osteoarthritis is not osteoarthrosis!) Osteoarthritis Cartilage.2013;21:16-21 Rosenthal AK. Crystals, inflammation, and osteoarthritis. Curr Opin Rheumatol.2011;23:170-3 Disclosure of Interest: None declared